UPAYA CEGAH STUNTING MELALUI PENERAPAN ISI PIRINGKU TERHADAP PENINGKATAN KADAR HEMAGLOBIN PADA REMAJA PUTRI DI MTS NEGERI 4 TANAH LAUT - oktariana, jayanti; Maolinda, Winda; Hidayah, Nur (Midwifery And Complementary Care, 2024)
Background: Nutritional problem that threatens the quality of life Stunting is a chronic malnutrition process that has a short-term impact in the form of a condition of failure to grow and a long-term impact in the form of low productivity in young adulthood and the risk of developing degenerative diseases. Stunting is a serious concern at this time, especially in developing countries such as Indonesia. Objective: To prevent stunting through the application of the contents of my plate to increase hemoglobin levels in young women of MTS Negeri 4 Tanah Laut. Methods: a quasi-experimental study, namely onegroup pretest posttest design, with a sample of 30 people all will be checked for hemoglobin levels. 10 samples of students who had hemoglobin levels <12 gr/dL, 10 samples were randomly sampled for control but were not treated. Results: Application of plate contents was proven to affect the hemoglobin levels of young women, proving that this application pringku can increase hemoglobin levels in young women, Hemoglobin levels of young women MTSN Tanah Laut were proven to increase by an average of 2.36 gr / dl, the party that has the most important role in improving the nutrition of children, especially adolescents, is the parents. Conclusion: the school always reminds its students about healthy food and their diet. Parents understand, understand the importance of maintaining their children's health, not just being fed, but must be maintained nutrition, protein and so on so that children's growth and development can run well. Keywords: adolescents, nutrition, stunting.